2020
DOI: 10.1016/j.jum.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, smart work, and collaborative space: A crisis-opportunity perspective

Abstract: In this essay, I employ a crisis-opportunity perspective to approach the practice of smart work and the making of collaborative space in responding and adapting to COVID-19. These trends have been emerging at a faster pace in the recent decade, facilitated by a growing knowledge economy and information technological advancement. COVID-19 provides an extreme setting to test and trigger changes, and are likely to translate these emerging trends into a new normal in the way we work and the way we use space. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 6 publications
1
32
0
2
Order By: Relevance
“…Urban mobility as well as any other type of travel in all spatial scales are significantly reduced during periods of spreading of infectious diseases like COVID-19 ( Abu-Rayash & Dincer, 2020 ; Beria & Lunkar, 2021 ; Bucsky, 2020 ; Shakibaei et al., 2021 ). The insecurity of people facing the danger of infection combined with travel restrictions imposed on them by the governments shape novel mobility behaviors on a global scale ( Beck & Hensher, 2020 ; Hu, 2020 ; Pawar, Yadav, Akolekar, & Velaga, 2020 ). During the pandemic, there has been a turn to private modes (cars, bikes, and motorbikes) and a decrease in the demand for public transport ( Hasselwander et al., 2021 ; Meena, 2020 ; Przybylowski, Stelmak, & Suchanek, 2021 ; Rajput, Li, Gao, & Mostafavi, 2021 ; Wilbur et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urban mobility as well as any other type of travel in all spatial scales are significantly reduced during periods of spreading of infectious diseases like COVID-19 ( Abu-Rayash & Dincer, 2020 ; Beria & Lunkar, 2021 ; Bucsky, 2020 ; Shakibaei et al., 2021 ). The insecurity of people facing the danger of infection combined with travel restrictions imposed on them by the governments shape novel mobility behaviors on a global scale ( Beck & Hensher, 2020 ; Hu, 2020 ; Pawar, Yadav, Akolekar, & Velaga, 2020 ). During the pandemic, there has been a turn to private modes (cars, bikes, and motorbikes) and a decrease in the demand for public transport ( Hasselwander et al., 2021 ; Meena, 2020 ; Przybylowski, Stelmak, & Suchanek, 2021 ; Rajput, Li, Gao, & Mostafavi, 2021 ; Wilbur et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding teleworking, it provides the employees with a flexible schedule; however, it may lead to diminished boundaries between private and professional life, causing an imbalance between personal concerns and work duties [119]. However, a survey done by Hu [120] showed that one of the main benefits of remote working is improving work-life balance and this may even lead to improving productivity. Despite this, organizational cultures and morals could be negatively affected by long-term remote working [83].…”
Section: The Inefficiency Of Education and Remote Workingmentioning
confidence: 99%
“…Safety concerns, anxiety, and stress level increased in society regarding using public transport after the beginning of the pandemic. In addition, it was suggested [10] that continuing remote working conditions might be a better option during the pandemic and even in the future. It is clearly seen that the COVID-19 pandemic has a significant influence on travel patterns and causes people to use private vehicles more [9].…”
Section: Introductionmentioning
confidence: 99%